Clinical bioethics : women facing the challenges of current clinical bioethics - López-Ibor Aliño, Blanca (2020)
Women can contribute to the current challenges of clinical bioethics a humanistic vision in relation to their capacity to welcome, care and give life. A complementary vision to which the man can contribute to which he adds his life experience as a woman.This publication aims to give some keys to face and solve the multiple bioethical questions that in the current clinic are raised at a time in history where relativism also affects human life. Training, cunning, courage and coherence are necessary when defending a bioethic based on the person, it is the dignity that is its own. Various situations are reviewed in clinical practice in which women can not only defend life, but also convince those who do not defend it with a good argument.